The effect of ionising radiation on the explosives: TATB, HMX and PETN - Lewis, Daniel A. (Cranfield University, 2019)
The effect ionizing radiation, specifically gamma, has on three of the most well known explosive materials; HMX, PETN and TATB, has been studied experimentally and computationally. Samples of these explosives that had been irradiated in vacuum to a total dose (equivalent to water) of 200 kGy by an average incident energy of 1.25 MeV, showed changes to their explosive and physical properties to varying degrees, with sensitivity to impact being most notably changed for PETN and HMX. Changes to the thermal properties of HMX and TATB, alongside the detection of long lived radicals for TATB and PETN, suggests alterations to each material’s chemistry. Changes were only detectable in solid state analytical methods, indicating that alterations to these materials are isolated within this state. Through comparison with other data, these changes appear to be highly dependant on the gaseous environment in which they are irradiated, with vacuum having the most significant effect. The widely reported greening of TATB under the influence of gamma (and ultraviolet and x-Ray) irradiation was found to be reversible upon re-crystallisation, with the process also appearing to remove the long lived radical that had existed in the material for over eight years. Radical concentration appears to correlate with total absorbed dose along with the level of green within the material. Computational investigation attributes the discolouration of TATB to the cationic radical derivative of TATB, which is stabilised by de-localised pi-bonding resonance of the constitutive aromatic ring, it is also suggested that this is the source of the radical signal observed in ESR analysis.Further computational investigation suggests that purported decomposition products of TATB such as the mono-furazan, mono-nitroso and phenoxyl radical are not the source of the discolouration and are also not thermodynamically favourable, unless the monofurazan or phenoxyl derivatives are in a cationic form. Thermodynamic evaluation of potential decomposition pathways for PETN and HMX yield a selection of energetically favourable products, however the significant majority are, like TATB, in the cationic radical form. Simulated ESR spectra for purported HMX decomposition products did not agree with those observed in literature, attributed to their short lived nature. However a measured long lived radical in TATB is attributed to the cationic radical form of TATB, the purported source of the discolouration. A long lived radical in PETN was also measured and assigned to the cation derivative of PETN by comparison with computational predictions.
© Cranfield University, 2019
Keywords: HMX - explosive; TATB - explosive; Pentaerythriltoltranitrate (PETN); Irradiation; Explosives